Effect of side effects antituberculosis preparations on upshots of the treatment patients with multidrug-resistant tuberculosis, who had received treatment on scheme of the program DOTS-PLUS - D. Yu. Schegertsov; Ye. V. Nekrasov; G. V. Yanova; O. V. Filinyuk; L. N. Buinova; O. V. Anastasov; Ye. P. Stepanova; I. G. Felker (Бюллетень сибирской медицины)
At treatment of patients with multidrug-resistant tuberculosis of lungs on scheme of the program DOTS-PLUS was noted development that or other side reaction on the part of organs and systems. We studied temper, frequency of the development of side effect upon upshot of the treatment beside by 101 patients in process of stationary course of the treatment.